2021
DOI: 10.1177/10738584211015136
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Pathophysiology of Neurological and Psychiatric Complications of COVID-19 Using Brain Organoids

Abstract: Neuropsychiatric manifestations of coronavirus disease 2019 (COVID-19) have been increasingly recognized. However, the pathophysiology of COVID-19 in the central nervous system remains unclear. Brain organoid models derived from human pluripotent stem cells are potentially useful for the study of complex physiological and pathological processes associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) as they recapitulate cellular heterogeneity and function of individual tissues. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Beyond autopsy studies, brain organoids have also expanded our understanding of viral neurotropism ( Ng et al, 2021 ). The first obstacles to viral penetration into the CNS are the BBB and blood-cerebrospinal fluid (CSF) barriers, which regulate entry of material into the brain.…”
Section: Sars-cov-2 Neurotropismmentioning
confidence: 99%
“…Beyond autopsy studies, brain organoids have also expanded our understanding of viral neurotropism ( Ng et al, 2021 ). The first obstacles to viral penetration into the CNS are the BBB and blood-cerebrospinal fluid (CSF) barriers, which regulate entry of material into the brain.…”
Section: Sars-cov-2 Neurotropismmentioning
confidence: 99%
“…However, the central role of the ACE2 receptor for SARS-CoV-2 infection was confirmed several times. These studies also triggered several reviews (Sanclemente-Alaman et al, 2020; Ng et al, 2021;Caporale and Testa, 2021;Willner et al, 2021;Bodnar et al, 2021;Harschnitz and Studer, 2021;Ramani et al, 2021;Chen et al, 2021).…”
Section: Brain Organoids Pioneered Knowledge On Sars-cov-2 Brain Infectionmentioning
confidence: 83%
“…have provided several crucial pieces of evidence on the effects of SARS-CoV-2 on the brain." (Ng et al, 2021). Projects including MPSCoRe and the COVID-19 AOP development in the CIAO project, the upcoming 1 st MPS World Summit 19 in 2022, and the creation of an international MPS society will further data collection and awareness of the part MPS can play in providing understanding of SARS-CoV-2 and its pathways.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurological symptoms and sequelae, during or after SARS-CoV-2 infection, have been reported [ 66 , 67 ]. Whether SARS-CoV-2 infection causes these complications through direct infection of the CNS or via a SARS-CoV-2-induced immune response is still unclear [ 65 , 68 ]. To investigate if the CNS is susceptible to direct infection, 8 out of 11 studies on SARS-CoV-2 (73%) reported on SARS-CoV-2 receptor expression in the CNS ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%